Self‐Propelled, High‐Crystalline Hydrogen‐Bonded Enzymatic Framework Assembled by Bottom‐Up Strategy - Huangsheng Yang; Jiahui Fu; Wei Huang; Tong Wu; Siming Huang; Guosheng Chen; Gangfeng Ouyang (Small Structures, 2023)
Biomimetic engineering presents an insightful strategy to access fascinating biocomposites integrating biological, chemical, and material functions. Herein, a new self‐propelled hydrogen‐bonded enzymatic framework through a biomimetic bottom‐up strategy is reported. The metal‐free, mesoporous, and photoactive hydrogen‐bonded organic framework (HOF) exoskeleton is in situ grown around catalase (CAT), an enzyme well known for its ability for the biocatalytic O2 generation. This HOF biomimetic method affords the ultrahigh encapsulation efficiency of CAT, yet well preserves the high crystallinity and periodically arranged mesochannels of HOF. The resultant hydrogen‐bonded enzymatic framework enables the self‐propelled motion with the help of a biocatalytic O2 bubble. Given the exquisite architecture, the HOF shell can serve as the dynamical sorbent for pollutant removal. More than that, it is showcased that the intrinsic photoactivity of HOF can be improved by the self‐propelled motion.